HUBUNGAN SANITASI LINGKUNGAN DAN FAKTOR BUDAYA DENGAN KEJADIAN DIARE PADA ANAK BALITA DI DESA TORIYO KECAMATAN BENDOSARI KABUPATEN SUKOHARJO - Siti Amaliah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2010)
Background: Occurrence of diarrhoea is high, specially for the five under years child at Bendosari PublicHealth Centre, which 30 % from Toriyo village.It caused probably by bed environment saniatation andcultural factor or habitual behaviour. Obyective: To analyse the correlation among environmentsanitation and cultural factor with the occurrence of diarrhea. Methods: The cross sectional design withcluster random sampling. The samples are 68 respondence of housewife.Independent variable are theenvironment sanitation and cultural factor. Dependent variable is incidence of diarrhea.Statistical analysewith Chi Square test. Result: The water supply using well dig 76,5 %, water of PDAM 23,5%. Faecesdisposal with good latrine 45,58 %, no having latrine 54,42 %. Drinking water which not be braised52,9%,stewed 47,1%.Cleaning the hand after defecate with soap 39,7%, not with soap 60,3%; cleaningthe hand with soap before eating 54,4%, not cleaning the hand 45,6 %. Treatment diarrhoea by self58,8%, treatment by Public Health Centre 41,2 % There are significant correlation among clean watersupply, coverage of bed latrine, drinking uncooked water, cleaning the hand with soap habits, andtreatment by self with occurrence of diarrhoea (p < 0,05). Conclusion: There are significant correlationamong environment sanitation and cultural factor with occurrence of diarrhoea.Keywords: diarrhoea, cultural factor, sanitation.